STREPTOCOCCAL TONSILLOPHARYNGITIS AT PRESENT — CLINICAL AND LABORATORY DATA - A. V. Aksenova (Klinicist)
Aim — to identify clinical features of streptococcal tonzillofaringitis (TF) using the scale of Centor, provide clinical and laboratory characteristicsof its outcomes to choose optimal antibiotic therapy.Materials and methods. The study included 386 patients with HF (183 men and 203 women). Scale Centor, bacteriological and immunologicalmethods were use to identify levels of antibodies to streptolysin O, polysaccharide A, glucuronic acid, dezoksiribonukleinaze B d.Results. All patients with HF were divided into groups with suspected viral and streptococcal etiology using Centor scale. By the result of complex bacteriological and immunological diagnosis of 13.5 % of patients with HF in the group with suspected viral etiology were moved into the group with streptococcal etiology. For this group as for group with suspected streptococcal etiology systemic antibiotic therapy was recommended.Conclusion. To complete the question about use of the antibiotic therapy in patients with TF clinical and laboratory examination should be a complete, including the use of the Centor scale. For patients with diagnosed streptococcal etiology of TF dispensary observation and primary prevention of rheumatic fever are required.